2009
DOI: 10.51347/jum.v14i1.3953
|View full text |Cite
|
Sign up to set email alerts
|

The study of urban form in Turkey

Abstract: Urban form is studied in a variety of disciplines in Turkey, but it has recently become central to urban studies. Histories of individual towns have usually been preoccupied with political, socio-economic and cultural issues. Archaeological excavations have made an important contribution to the reconstruction and analysis of Hellenistic, Roman, Byzantine and Turkish historic cities located in Anatolia and Thrace. Urban form is often considered as a container of socio-economic processes and as a marker in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This paper adopts space syntax techniques for reading the spatial patterns of urban fabrics. Space syntax is an approach to describing and analysing patterns of urban and architectural space, both at the architectural and urban scales (Kubat, 2010). The analysis of urban morphology and historical analysis of urban fabrics using space syntax technics was the subject of many studies (Aleksandrowicz, Yamu et al, 2018;Cheng and Wang, 2017;Hillier, Bill and Hanson, 1987;Kubat, 2010;Mohareb, 2016;Paul, 2014;Sahni, 2018) focusing on the definition of urban patterns through syntactic parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper adopts space syntax techniques for reading the spatial patterns of urban fabrics. Space syntax is an approach to describing and analysing patterns of urban and architectural space, both at the architectural and urban scales (Kubat, 2010). The analysis of urban morphology and historical analysis of urban fabrics using space syntax technics was the subject of many studies (Aleksandrowicz, Yamu et al, 2018;Cheng and Wang, 2017;Hillier, Bill and Hanson, 1987;Kubat, 2010;Mohareb, 2016;Paul, 2014;Sahni, 2018) focusing on the definition of urban patterns through syntactic parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Space syntax is an approach to describing and analysing patterns of urban and architectural space, both at the architectural and urban scales (Kubat, 2010). The analysis of urban morphology and historical analysis of urban fabrics using space syntax technics was the subject of many studies (Aleksandrowicz, Yamu et al, 2018;Cheng and Wang, 2017;Hillier, Bill and Hanson, 1987;Kubat, 2010;Mohareb, 2016;Paul, 2014;Sahni, 2018) focusing on the definition of urban patterns through syntactic parameters. For historical research, space syntax provides a way into conceptualising and thinking about the role of space and its relation to life in the built environment (Griffiths, 2012;Palaiologou and Griffiths, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies lack in-depth historico-geographical investigations of the shaping of the urban landscape. Kubat (2010) showed that there has been almost no investigation into the development of the urban form of Turkish cities from a fringe-belt perspective, though more recently a study has been undertaken by Hazar and Kubat (2015) on the fringe belts of İstanbul in comparison with those of Barcelona. In an earlier study of Mersin, Ünlü (2013) focused on morphological processes within its IFB.…”
Section: The Growth Of Mersin and The Interrelations Of Fringe Beltsmentioning
confidence: 99%
“…Over the past 16 years, articles in the series have been published on: i) nine European countries -Spain (Vilagrasa Ibarz, 1998), France (Darin, 1998), Italy (Marzot, 2002), Germany (Hofmeister, 2004), Great Britain (Larkham, 2006), Ireland (Kealy and Simms, 2008), Sweden (Abarkan, 2009), Poland (Koter and Kulesza, 2010) and Portugal (Oliveira et al, 2011); ii) two North American countries -United States (Conzen, 2001) and Canada (Gilliland and Gauthier, 2006); iii) one Asian country -South Korea (Kim, 2012); and finally, iv) one Oceanian country -Australia (Siksna, 2006). There was also an article by Kubat (2010) on Turkey, a country straddling two continents, part being in the Anatolian peninsula in Asia, and part in Thrace in South-Eastern Europe.…”
Section: The Contents Of the Articlesmentioning
confidence: 99%
“…Group 5 is a predominantly architectural perspective on Turkish cities (Kubat, 2010), giving attention to inter alia urban morphological theory and concepts.…”
Section: The Different Perspectivesmentioning
confidence: 99%